THE RELATIONSHIP BETWEEN READING INTEREST AND READING COMPREHENSION ABILITY OF GRADE XII OF AL-AZHAR SENIOR HIGH SCHOOL MEDAN IN THE 2024/2025 ACADEMIC YEAR - Dhea Zafira Ramadhani; Rizkia Zaky; Aura Kirana; Azzahra Davina; Celfyah Nhola; Faiz Muhammad Ilyas Setiadjed (CV. RADJA PUBLIKA, 2024)
The problem that will be studied in this journal is the relationship between reading interest and reading comprehension ability of class XII students at Al-Azhar Medan's Leading High School. The method used is a qualitative research approach by interviewing class XII students. This research was conducted in class 12 of Al-Azhar Medan's Leading High School. The population in this journal is 20 students. The purpose of this study was to determine how much influence reading interest has on reading comprehension ability. As well as completing assignments from the Pancasila Student Profile activity in the Merdeka Belajar curriculum. The results of the study indicate that there is a positive relationship between reading interest and the abilities of students in class XII of Al-Azhar Medan's Leading High School. This shows that the rise and fall of students' reading interest affects their ability to understand reading.